2013
DOI: 10.2337/dc13-0610
|View full text |Cite
|
Sign up to set email alerts
|

HbA1c and Risk of Severe Hypoglycemia in Type 2 Diabetes

Abstract: OBJECTIVEWe examined the association between HbA1c level and self-reported severe hypoglycemia in patients with type 2 diabetes.RESEARCH DESIGN AND METHODSType 2 diabetic patients in a large, integrated healthcare system, who were 30–77 years of age and treated with glucose-lowering therapy, were asked about severe hypoglycemia requiring assistance in the year prior to the Diabetes Study of Northern California survey conducted in 2005–2006 (62% response rate). The main exposure of interest was the last HbA1c l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
180
3
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 213 publications
(212 citation statements)
references
References 35 publications
(43 reference statements)
20
180
3
5
Order By: Relevance
“…The highest incidence was in those with the highest A1cs and was not related to whether or not the patient was on insulin, insulin plus an oral agent, or oral agents alone. 7 These observations and others have led the Endocrine Society and the American Diabetes Association to recommend that for "healthy adults with diabetes, a reasonable glycemic goal might be the lowest A1c that does not cause severe hypoglycemia, preserves awareness of hypoglycemia, and results in an acceptable number of documented episodes of symptomatic hypoglycemia." 8 The recent reduction of A1c goals in children and young adults with type 1 diabetes to <7.5% exert more pressure on finding a way to achieve those goals.…”
Section: The Problemmentioning
confidence: 99%
“…The highest incidence was in those with the highest A1cs and was not related to whether or not the patient was on insulin, insulin plus an oral agent, or oral agents alone. 7 These observations and others have led the Endocrine Society and the American Diabetes Association to recommend that for "healthy adults with diabetes, a reasonable glycemic goal might be the lowest A1c that does not cause severe hypoglycemia, preserves awareness of hypoglycemia, and results in an acceptable number of documented episodes of symptomatic hypoglycemia." 8 The recent reduction of A1c goals in children and young adults with type 1 diabetes to <7.5% exert more pressure on finding a way to achieve those goals.…”
Section: The Problemmentioning
confidence: 99%
“…For the assessment of hypoglycaemia incidence, a classification based on clinical data similar to those used in most of the studies, and thus it seems that in this survey the probability of overestimating hypoglycaemia incidence is negligible [22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…The rate of hypoglycemia in type 2 diabetes is higher than usually appreciated. [57][58][59] For example Lipska et al reported that 10.8% of patients in the large database experienced severe hypoglycemia. 59 Gehlaut et al found that 49% of patients with type 2 diabetes in their study had at least one episode of hypoglycemia during a 5-day analysis with CGM and many of those hypoglycemic episodes were asymptomatic.…”
Section: Evidence For General Benefit Of Cgm In Type 2 Diabetesmentioning
confidence: 99%
“…[57][58][59] For example Lipska et al reported that 10.8% of patients in the large database experienced severe hypoglycemia. 59 Gehlaut et al found that 49% of patients with type 2 diabetes in their study had at least one episode of hypoglycemia during a 5-day analysis with CGM and many of those hypoglycemic episodes were asymptomatic. 58 They also found that 21% of those patients found to have hypoglycemia had values <50 mg/dL and episodes were most common in those on insulin.…”
Section: Evidence For General Benefit Of Cgm In Type 2 Diabetesmentioning
confidence: 99%